ANGKA KEBERUNTUNGAN DAN ANGKA KESIALAN DALAM PEMAHAMAN ORANG TIONGHOA DIYOGYAKARTA - , SARTIKA IPAENIN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The concept of number is always taken into account by the Chinese, because those figures have a very deep meaning. Believe in the lucky numbers and unlucky numbers will always be there, because those numbers have the energy to be able to direct their life choices can even affect their behavior. Confidence in the figures often associated in the daily life of the Chinese, not foreign if the Chinese always connect even the smallest things in their lives with the numbers, but not all Chinese have the same understanding, there are some Chinese who do not believe in the existence of lucky numbers and unlucky numbers. Fundamental reason, every of the religion that they had good fortune, good luck, bad luck has been outlined by the Lord.